Patient-Centered Care in Family Medicine: Strategies for Continuity and Comprehensive Care for Older Adults – A Mixed-Methods Study - Alodhialah AM; Almutairi AA; Almutairi M (Clinical Interventions in Aging)
Abdulaziz M Alodhialah,1 Ashwaq A Almutairi,2 Mohammed Almutairi1 1Department of Medical-Surgical Nursing, College of Nursing, King Saud University, Riyadh, Saudi Arabia; 2School of Nursing & Midwifery, Monash University, Melbourne, AustraliaCorrespondence: Abdulaziz M Alodhialah, Email aalodhailah@ksu.edu.saIntroduction: Patient-centered care (PCC) is a crucial approach in family medicine, particularly for older adults with complex health needs. This study evaluates the implementation of PCC strategies and their impact on health outcomes for older adults in family medicine settings.Methods: A convergent parallel mixed-methods study was conducted, involving 47 healthcare providers and 126 older adult patients in Riyadh, Saudi Arabia. Quantitative data were collected using structured surveys, while qualitative data were obtained through semi-structured interviews. Statistical analyses included chi-square tests, ANOVA, and effect size calculations to assess the impact of PCC strategies.Results: Healthcare providers identified continuity of care programs (48.9%) and patient education (44.7%) as the most effective PCC strategies. Key challenges included time constraints (74.5%) and lack of resources (59.6%). Patients in the high PCC implementation group demonstrated significantly better health outcomes, including lower hospital readmission rates (15.9% vs 36.5%, p=0.002), improved chronic disease management (87.3% vs 66.7%, p=0.014), higher adherence to care plans (82.5% vs 60.3%, p=0.008), and increased patient satisfaction scores (mean 4.6 vs 3.9, p=0.001). Qualitative findings highlighted key themes, including communication challenges, patient empowerment, and the role of multidisciplinary teams.Discussion: PCC strategies significantly enhance health outcomes and patient satisfaction among older adults in family medicine. However, implementation barriers such as time constraints, resource limitations, and coordination challenges must be addressed. The study underscores the need for systemic healthcare reforms to improve PCC delivery.Conclusion: This study highlights the benefits of PCC in improving patient outcomes and satisfaction while identifying barriers that must be addressed for effective implementation. Greater investment in PCC initiatives, improved healthcare coordination, and professional training are essential to enhancing care quality for older adults.Keywords: patient-centered care, family medicine, older adults, healthcare outcomes, mixed-methods study